Evaluating the Effects of Fibrinogen αC Mutations on the Ability of Factor XIII to Crosslink the Reactive αC Glutamines (Q237, Q328, Q366) - Mouapi, Kelly Njine; Wagner, Lucille J.; Stephens, Chad A.; Hindi, Mohammed M.; Wilkey, Daniel W.; Merchant, Michael L.; Maurer, Muriel C. (Thrombosis and Haemostasis, 2019)
Fibrinogen (Fbg) levels and extent of fibrin polymerization have been associated with various pathological conditions such as cardiovascular disease, arteriosclerosis, and coagulation disorders. Activated factor XIII (FXIIIa) introduces γ-glutamyl-ε-lysinyl isopeptide bonds between reactive glutamines and lysines in the fibrin network to form a blood clot resistant to fibrinolysis. FXIIIa crosslinks the γ-chains and at multiple sites in the αC region of Fbg. Fbg αC contains a FXIII binding site involving αC (389–402) that is located near three glutamines whose reactivities rank Q237 >> Q366 ≈ Q328. Mass spectrometry and two-dimensional heteronuclear single-quantum correlation nuclear magnetic resonance assays were used to probe the anchoring role that αC E396 may play in controlling FXIII function and characterize the effects of Q237 on the reactivities of Q328 and Q366. Studies with αC (233–425) revealed that the E396A mutation does not prevent the transglutaminase function of FXIII A2 or A2B2. Other residues must play a compensatory role in targeting FXIII to αC. Unlike full Fbg, Fbg αC (233–425) did not promote thrombin cleavage of FXIII, an event contributing to activation. With the αC (233–425) E396A mutant, Q237 exhibited slower reactivities compared with αC wild-type (WT) consistent with difficulties in directing this N-terminal segment toward an anchored FXIII interacting at a weaker binding region. Q328 and Q366 became less reactive when Q237 was replaced with inactive N237. Q237 crosslinking is proposed to promote targeting of Q328 and Q366 to the FXIII active site. FXIII thus uses Fbg αC anchoring sites and distinct Q environments to regulate substrate specificity.
Keywords: fibrinogen αC; factor XIII; coagulation; mass spectrometry; nuclear magnetic resonance